2006
DOI: 10.1021/jf0521855
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids as Mushroom Tyrosinase Inhibitors:  A Fluorescence Quenching Study

Abstract: Flavonoids, a group of naturally occurring antioxidants and metal chelators, can be used as tyrosinase inhibitors due to their formation of copper-flavonoid complexes. Thus, to investigate the underlying inhibition mechanism, a large group of flavonoids from several major flavones and flavonols were tested using fluorescence quenching spectroscopy. In addition, large differences in the tyrosinase inhibitory activities and chelating capacities according to the location of the hydroxyl group(s) in combination wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(142 citation statements)
references
References 38 publications
7
131
0
4
Order By: Relevance
“…In a word, The results based on molecular docking further validated that salidroside didn't react with copper ions located in the active center of tyrosinase, which was in accordance with the conclusion achieved by UV spectrum. In addition, Donghyun Kim et al had found that some flavonoids had a high inhibition to tyrosinase, which was related to the ability to form chelate with copper ions [35]. However, in this experiment, the inhibition of salidroside on tyrosinase was only up to 33.04%.…”
Section: Molecular Modeling For the Binding Of Salidroside With Tyrosmentioning
confidence: 54%
See 3 more Smart Citations
“…In a word, The results based on molecular docking further validated that salidroside didn't react with copper ions located in the active center of tyrosinase, which was in accordance with the conclusion achieved by UV spectrum. In addition, Donghyun Kim et al had found that some flavonoids had a high inhibition to tyrosinase, which was related to the ability to form chelate with copper ions [35]. However, in this experiment, the inhibition of salidroside on tyrosinase was only up to 33.04%.…”
Section: Molecular Modeling For the Binding Of Salidroside With Tyrosmentioning
confidence: 54%
“…Keep temperature of 30°C for 10 min. Finally, Scan ultraviolet-visible spectrum of each mixture respectively in the wavelength of 200-600 nm in the reaction of 0, 10, 20, 30, and 40 min [30,31].…”
Section: Uv-vis Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…In the ultraviolet chromatogram, the wavelength of maximum absorption of the inhibitors will exhibit redshift. The excessive Cu 2+ added in the flavonol, the inhibitor chelated with Cu 2+ , the characteristic absorption peaks of the flavonol were moved toward longer wavelength (Kim et al 2006b). According to this feature, the effect of Cu 2+ and tyrosinase on the UV-visible spectrum of the ethyl acetate extract are shown in Fig.…”
Section: Tyrosinase On the Uv Visible Spectrum Of The Ethyl Acetate Ementioning
confidence: 99%